ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA JURUSAN MANAJEMEN BISNIS STIE MIKROSKIL DALAM KEIKUTSERTAAN BISNIS MULTI LEVEL MARKETING - Hanny Siagian (Business Management Journal, 2016)
The research objective is to identify and analyze the factors that affectingthe interest of business management student of STIE Mikroskil in participating Multi Level Marketing (MLM) business. The method used in this study is a survey approach, this kind of research is a quantitative and descriptive explanatory. The methods of data collection is done by providing a list of written questions and documentation study. Data analysis method used is multiple linear regression using SPSS software. The results of the research that has been carried out simultaneously showed that a small capital, flexible time, require experience and be able to determine the income have significant impact on the STIE Mikroskil student's decision. Partially small capital has positive and significant impact on student's decision. Time flexible partially has positive and significant impact on student's decision. Partially do not require experience has positive and significant impact on student's decision. Partially,be able to determine the income has positive and significant impact on student's decision. This research showed that the income can determine a positive impact on improving student's decision.Keywords: small capital, flexible time, require experience, be able to determine the income and student’s decision